The effect of an organizational level participatory intervention in secondary vocational education on work-related health outcomes: results of a controlled trial - Roosmarijn M. C. Schelvis; Noortje M. Wiezer; Allard J. van der Beek; Jos W. R. Twisk; Ernst T. Bohlmeijer; Karen M. Oude Hengel (BMC, 2017)
Abstract Background Work-related stress is highly prevalent in the educational sector. The aim of the current study was to evaluate the effectiveness of an organizational level, participatory intervention on need for recovery and vitality in educational workers. It was hypothesized that the intervention would decrease need for recovery and increase vitality. Methods A quasi-experiment was conducted at two secondary Vocational Education and Training schools (N = 356) with 12- and 24-months follow-up measurements. The intervention consisted of 1) a needs assessment phase, wherein staff and teachers developed actions for happy and healthy working under supervision of a facilitator, and 2) an implementation phase, wherein these actions were implemented by the management teams. Mixed model analysis was applied in order to assess the differences between the intervention and control group on average over time. All analyses were corrected for baseline values and several covariates. Results No effects of the intervention were found on need for recovery, vitality and most of the secondary outcomes. Two small, statistically significant effects were in unfavorable direction: the intervention group scored on average over time significantly lower on absorption (i.e. a subscale of work engagement) and organizational efficacy than the control group. Conclusions Since no beneficial effects of this intervention were found on the primary and most of the secondary outcomes, further implementation of the intervention in its current form is not eligible. We recommend that future organizational level interventions for occupational health 1) incorporate an elaborate implementation strategy, 2) are more specific in relating actions to stressors in the context, and 3) are integrated with secondary preventive, individual focused stress management interventions. Trial registration Netherlands Trial Register NTR3284 (date registered: February 14 2012).